Scotland and the wider world : essays in honour of Allan I. Macinnes - McIntyre, Neil; Cathcart, Alison; Macinnes, Allan I. (Studies in early modern cultural, political and social history ;, 2022)
As one of the most prolific historians of his generation, Allan I. Macinnes, Emeritus Professor of History at the University of Strathclyde, has been foremost in promoting an international rather than insular approach to the study of Scotland. In a distinguished career he has written extensively on the Scottish Highlands, the British revolutions, the formation of the United Kingdom, the Jacobite movement, and Scottish involvement in the British Empire. The chapters collected here reflect the extent of these interests and a commitment to understanding Scotland - or indeed, other territorial units - in an international or global context. Covering a period from the sixteenth to the nineteenth century, essays examine the complex interaction of the peoples of the British and Irish isles; they consider Scottish participation in Britannic and European conflict; and they explore Scottish involvement in business networks, political unions, and maritime empires. From intellectual and cultural exchange to political and military upheaval, Scotland and the Wider World will be key reading for anyone interested in the antecedents to Scotland's current international standing.--